The Politicization of COVID-19 Omicron: Southern Africa Tourism Sector - Musavengane, Regis (Africa Journals, 2022)
The Covid-19 virus has impacted the tourism sector heavily. The pandemic provided a fertile ground for politicians, development experts and individuals to ‘open’ up and share their emotions. In this article, discourse analysis is used to decipher the politicization of the COVID-19 Omicron variant and its impacts on the tourism Southern African tourism sector. Data is collected from the social media platforms, chiefly, Twitter. The approaches taken by countries that harshly banned travel to the Southern Africa have been described as Afrophobia, anti-scientific and fear and anti-development of the Southern African tourism sector. There is a general agreement among the voices of the participants that the strands of injustice and mistrust still exist among nations and politicians, a situation which is detrimental to tourism development